2022
DOI: 10.1038/s41467-022-29840-1
|View full text |Cite
|
Sign up to set email alerts
|

The barley leaf rust resistance gene Rph3 encodes a predicted membrane protein and is induced upon infection by avirulent pathotypes of Puccinia hordei

Abstract: Leaf rust, caused by Puccinia hordei, is an economically significant disease of barley, but only a few major resistance genes to P. hordei (Rph) have been cloned. In this study, gene Rph3 was isolated by positional cloning and confirmed by mutational analysis and transgenic complementation. The Rph3 gene, which originated from wild barley and was first introgressed into cultivated Egyptian germplasm, encodes a unique predicted transmembrane resistance protein that differs from all known plant disease resistanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 113 publications
0
29
0
Order By: Relevance
“…Morex, while Morex is susceptible to P. hordei pathotype 5457 P+, the RphGID locus may not exist in this accession. Many disease resistance genes isolated so far such as the genes conferring resistance to Xanthomonas bacteria in rice and pepper ( Yoshimura et al, 1998 ; Wu et al, 2008 ; Wang et al, 2015 , 2018 ), and especially the barley leaf rust resistance gene Rph3 ( Dinh et al, 2022 ) encode other types of protein without any conserved domains. In our study, we were not able to pinpoint whether all the identified genes in ORF region play role in providing resistance against all the six pathotypes used in this study and therefore further studies on validation of these genes is highly recommended.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Morex, while Morex is susceptible to P. hordei pathotype 5457 P+, the RphGID locus may not exist in this accession. Many disease resistance genes isolated so far such as the genes conferring resistance to Xanthomonas bacteria in rice and pepper ( Yoshimura et al, 1998 ; Wu et al, 2008 ; Wang et al, 2015 , 2018 ), and especially the barley leaf rust resistance gene Rph3 ( Dinh et al, 2022 ) encode other types of protein without any conserved domains. In our study, we were not able to pinpoint whether all the identified genes in ORF region play role in providing resistance against all the six pathotypes used in this study and therefore further studies on validation of these genes is highly recommended.…”
Section: Discussionmentioning
confidence: 99%
“…The total DNA from leaf samples was extracted using the SDS method as previously described by Dinh et al (2022) . About 30 mg of the first leaf of each seedling was sampled into a 96-well collection tube (12 × 8 wells) containing two ball bearings and subjected to DNA extraction using an SDS method.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations